IMPLEMENTASI PROGRAM TAZKIYAH AL-NAFS DI MADRASAH DINIYAH SALAFIYAH BAALAWY DALAM MENANAMKAN KECERDASAN SPIRITUAL BAGI SANTRI - Gio Apriansyah; Ismail Sukardi; Nyayu Soraya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify and analyse the implementation of the tazkiyah al-nafs program at the Salafiyah Baalawy Islamic Junior High School in instilling spiritual intelligence for students. In this context, the tazkiyah al-nafs programme carried out at the Salafiyah Baalawy Madrasah aims to cleanse the hearts of students from bad traits or prejudices of students which include hasud, arrogance, suudzon, takabbur, ujub, riya', ghazab and emptying the soul of all thoughts that will distract from remembrance and remembering Allah. This research is located in Baalawy Building, Jl. Sei Bayas 10 Ilir, Ilir Timur II District, Palembang city. This research method uses qualitative methods. Data was collected using observation, interview and documentation methods. The data analysis used in the research includes data collection, data presentation and conclusion. The results showed that the implementation of the tazkiyah al-nafs programme took place in three stages, namely the takhalliyat al-nafs stage, the tahalliyat al-nafs stage, and the tajalliyat al-nafs stage. And using the method of habituation, supervision and punishment. And the positive impact of this tazkiyah al-nafs programme is that students can keep themselves away from evil deeds and sin. As well as students will be elevated in the side of Allah and in front of fellow human beings, because they are able to become human beings who behave praiseworthy and noble, can create benefits, safety and welfare in life.